Update on Anticoagulation Strategies in Patients with ECMO—A Narrative Review - Šoltés, Ján; Skribuckij, Michal; Říha, Hynek; Lipš, Michal; Michálek, Pavel; Balík, Martin; Pořízka, Michal (Journal of clinical medicine, 2023)
The use of extracorporeal membrane oxygenation (ECMO) has recently increased exponentially. ECMO has become the preferred mode of organ support in refractory respiratory or circulatory failure. The fragile balance of haemostasis physiology is massively altered by the patient’s critical condition and specifically the aetiology of the underlying disease. Furthermore, an application of ECMO conveys another disturbance of haemostasis due to blood-circuit interaction and the presence of an oxygenator. The purpose of this review is to summarise current knowledge on the anticoagulation management in patients undergoing ECMO therapy. The unfractionated heparin modality with monitoring of activated partial thromboplastin tests is considered to be a gold standard for anticoagulation in this specific subgroup of intensive care patients. However, alternative modalities with other agents are comprehensively discussed. Furthermore, other ways of monitoring can represent the actual state of coagulation in a more complex fashion, such as thromboelastometric/graphic methods, and might become more frequent. In conclusion, the coagulation system of patients with ECMO is altered by multiple variables, and there is a significant lack of evidence in this area. Therefore, a highly individualised approach is the best solution today.